Multi-scale investigation of stainless-steel passivation in seawater concrete pore solution - Jiahong Wei; Quanming Fu; Duowen Chen; Xutao Wang; Wenkai Cao; Di Xu; Haibing Zheng (Case Studies in Construction Materials)
Stainless-steel bars can be effectively used in seawater sea sand concrete due to their excellent resistance to chloride ions, contributing to resource conservation and sustainable development. However, the underlying impact mechanism of chloride ion on the passivation of stainless steel in seawater sea sand concrete has not been thoroughly studied. In this work, a multi-scale study was carried out to reveal the role of chloride ion on the passivation of stainless-steel bar in concrete. At the macro level, the presence of chloride ions reduced the corrosion resistance of the stainless-steel passive film, but did not cause corrosion. On the micro level, chloride ion interfered with the phase transformation of the passive film, increased Cr oxides and decreased the loose Fe3 + oxides. From the atomic view of point, the incorporation of chloride into the passive film was mainly due to the higher adsorption energy of Fe2O3 and Cr2O3 with chloride ion, increasing the reactivity of passive film. The presence of Mo in the outer layer of passive film presented a much lower adsorption energy of chloride compared with Fe2O3 and Cr2O3, impeding the ingress of chloride ion in the inner layer. Density functional theory (DFT) calculation complimented the knowledge of interaction of chloride ion with the passive film.